Digital Parenting: The Role of Technology in Shaping Modern Child Rearing - Oliver Henry Cooper; Mason William Tate; Liam Hudson (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
With the rise of digital media, parenting strategies have evolved to incorporate technology in child-rearing practices. This paper examines the role of digital tools, such as parental control apps, online safety guidelines, and educational platforms, in modern parenting. The study explores the balance between screen time and healthy child development, providing recommendations for responsible digital parenting.